Use of Ages and Stages Questionnaires™ (ASQ) in a Navajo population: Comparison with the U.S. normative dataset. (1st August 2019) - Nozadi, Sara S.; Li, Li; Clifford, Jantina; Du, Ruofei; Murphy, Kimberly; Chen, Lu; ,; Seanez, Paula; Burnette, Courtney; MacKenzie, Debra; Lewis, Johnnye L.
Abstract: Background: The Ages and Stages Questionnaires‐Third Edition (ASQ‐3) is a parent‐completed screening to identify young children at‐risk for developmental delays in the United States and internationally. Federal programs operating on Navajo Nation use the ASQ‐3 to determine the need for early intervention services, even though the ASQ‐3 national sample used to establish cutoff scores for referral included only 1% Native American children. Objectives: The current study aimed to compare the ASQ‐3 results from a sample of Navajo infants to those from a representative national U.S. sample and to examine the specificity and sensitivity of the ASQ‐3 in Navajo population. Methods: The sample included 530 Navajo infants (47.3% males) aged between 1 and 13 months who lived in remote and rural areas across the Navajo Nation. Children's development was assessed during home visits at 2‐, 6‐, 9‐, and 12‐month assessment windows. Results: Results showed that after 6 months, Navajo children had lower mean scores and higher percentages of children at‐risk for developmental delays than those from the national sample. The sensitivities and specificities, estimated using a Bayesian diagnostic approach under both conservative and nonconservative prior range choices, suggested a comparable validity performance to that from other ASQ‐3 studies. Discussion: The results of this study along with our ongoing comprehensive assessments at 4 years of age inform current programs working with Navajo children to improve early identification of developmental delays.